Patient's performance status should dictate transfusion strategy in nonvariceal acute upper gastrointestinal bleeding (NV-AUGIB): A prospective multicenter cohort study: Transfusion strategy in NV-AUGIB. Issue 10 (October 2020) - Marmo, Riccardo; Soncini, Marco; de Franchis, Roberto; ,
Abstract: Background: Non-variceal acute UGI bleeding (NV-AUGIB) is a frequent indication for transfusion, but the best hemoglobin threshold and target values for transfusion in relation to the patients' performance status are unknown. Objective: To identify threshold and target hemoglobin levels for transfusion favoring survival of patients with NV-AUGIB stratified by ASA score. Design: Prospective cohort study. Setting: 50 hospitals of the Italian National Health Service. Participants: 2758 consecutive patients with NV-AUGIB admitted to 50 Italian hospitals from January 1st, 2014 to December 31st, 2015. Five hemoglobin cut-off values were evaluated. Results: 30-days mortality: overall: 5.4%; ASA 1–2 patients: 2.5%; ASA 3–4 patients: 10.8%. Mortality was higher when hemoglobin at admission was ≤ 7 g/dL in ASA 1–2 patients, and when it was ≤ 8 g/dL in ASA 3–4 patients. The hemoglobin levels after transfusion favouring survival were ≥ 8 g/dL in ASA 1–2, p <0.0001 and 9–10 g/dL in ASA 3–4 patients; p  = 0.0002. Conclusions: In patients with NV-AUGIB the physical performance status should dictate the transfusion strategy. In ASA 1–2 patients, admission hemoglobin values ≤ 7 g/dL should prompt transfusion, aiming at a target value of 8–9 g/dL; the corresponding figures for ASA 3–4 patients are: admission hemoglobin level ≤ 8 g/dL and target value of 9–10 g/dL.